Section A.6 Partial Fraction Decomposition
Partial fraction decomposition is a method used to express a rational function as a sum of simpler fractions. This process is especially useful when solving integrals and applying inverse Laplace transforms. The following steps outline the process to find the partial fraction decomposition of a rational function.
- Check the Degree of the Numerator and Denominator
Ensure the degree of the numerator is less than the degree of the denominator. If the numerator has a degree greater than or equal to the denominator, first perform polynomial long division to reduce the degree of the numerator.
- Factor the Denominator
Factor the denominator into irreducible linear or quadratic factors.
- Set up the Partial Fraction Decomposition
Based on the factors of the denominator, write the decomposition:
For each linear factor
\((s - a)\text{,}\) include a term of the form
\begin{equation*}
\frac{A}{s - a}\text{.}
\end{equation*}
For repeated linear factors
\((s - a)^n\text{,}\) include terms like:
\begin{equation*}
\frac{A_1}{s - a} + \frac{A_2}{(s - a)^2} + \dots + \frac{A_n}{(s - a)^n}.
\end{equation*}
For irreducible quadratic factors
\((s^2 + bs + c)\text{,}\) include a term of the form
\begin{equation*}
\frac{Bs + C}{s^2 + bs + c}\text{.}
\end{equation*}
For repeated quadratic factors
\((s^2 + bs + c)^n\text{,}\) include terms like:
\begin{equation*}
\frac{B_1s + C_1}{s^2 + bs + c} + \frac{B_2s + C_2}{(s^2 + bs + c)^2} + \dots + \frac{B_ns + C_n}{(s^2 + bs + c)^n}.
\end{equation*}
- Solve for the Constants
Multiply both sides of the equation by the common denominator and expand to eliminate fractions. Group terms by powers of \(s\) and set up a system of equations to solve for the unknown constants \(A\text{,}\) \(B\text{,}\) and \(C\text{.}\)
- Final Result
Once the constants are found, write the final partial fraction decomposition. This decomposition can now be used for further calculations such as integrals or inverse Laplace transforms.
Reference: Partial Fraction General Form Terms.
For each type of factor in the denominator, add the following terms to the partial fraction decomposition:
\(\ds\frac{A_1}{s - a} + \frac{A_2}{(s - a)^2} + \dots + \frac{A_n}{(s - a)^n}\)
\(\ds\frac{Bs + C}{s^2 + bs + c}\)
\(\ds\frac{B_1s + C_1}{s^2 + bs + c} + \dots + \frac{B_ns + C_n}{(s^2 + bs + c)^n}\)
Example A.7.
Find the partial fraction decomposition form for each.
\(\ds\frac{8x^2 - 51x + 41}{x^2 - 6x + 5}\) Solution. Solution
First, factor the denominator:
\begin{equation*}
x^2 - 6x + 5 = (x - 5)(x - 1).
\end{equation*}
The denominator has the following factors:
\(x-5\) (linear, single)
\(x-1\) (linear, single)
Hence, the FORM of the partial fraction decomposition is:
\begin{equation*}
u(x) = \frac{A}{x-5} + \frac{B}{x-1}.
\end{equation*}
\(\ds\frac{17x - 11}{x^2(x-3)} \qquad\) Solution. Solution
Since the denominator is already factored, we see that the denominator has the following factors:
Hence, the FORM of the partial fraction decomposition is:
\begin{equation*}
g(x) = \frac{A}{x} + \frac{B}{x^2} + \frac{C}{x-3}.
\end{equation*}
\(\ds\frac{x+12}{(x^2 - 4)^2} \qquad\) Solution. Solution
Here we need to finish factoring the denominator:
\begin{equation*}
h(x) = \frac{x+12}{(x^2 - 4)^2} = \frac{x+12}{[(x-2)(x+2)]^2} = \frac{x+12}{(x-2)^2(x+2)^2}
\end{equation*}
Now we see that the denominator has the following factors:
\((x-2)\) (linear, double)
\((x+2)\) (linear, double)
Hence, the FORM of the partial fraction decomposition is:
\begin{equation*}
h(x) = \frac{A}{x-2} + \frac{B}{(x-2)^2} + \frac{C}{x+2} + \frac{D}{(x+2)^2}.
\end{equation*}
\(\ds\frac{3x-14}{(x+1)(x^2 + 2x + 1)} \qquad\) Solution. Solution
Here we need to finish factoring the denominator:
\begin{equation*}
r(x) = \frac{3x-14}{(x+1)(x^2 + 2x + 1)} = \frac{3x-14}{(x+1)(x+1)(x+1)} = \frac{3x-14}{(x+1)^3}
\end{equation*}
Now we see that \((x+1)\) (which is linear), is a factor (three times) of the denominator. Hence, the FORM of the partial fraction decomposition is:
\begin{equation*}
r(x) = \frac{A}{x+1} + \frac{B}{(x+1)^2} + \frac{C}{(x+1)^3}.
\end{equation*}
Example A.8.
Find the partial fraction decomposition of
\begin{equation*}
\frac{5s + 3}{(s - 1)(s^2 + s + 1)}\text{.}
\end{equation*}
Solution. Solution
Factor the denominator as
\begin{equation*}
(s - 1)(s^2 + s + 1)\text{.}
\end{equation*}
The partial fraction decomposition is:
\begin{equation*}
\frac{5s + 3}{(s - 1)(s^2 + s + 1)} = \frac{A}{s - 1} + \frac{Bs + C}{s^2 + s + 1}.
\end{equation*}
Multiply through by \((s - 1)(s^2 + s + 1)\) and solve for \(A\text{,}\) \(B\text{,}\) and \(C\text{.}\)
\begin{equation*}
5s + 3 = A(s^2 + s + 1) + (Bs + C)(s - 1).
\end{equation*}
Expanding and comparing coefficients, we find:
\begin{equation*}
A = 5, \quad B - A = 0, \quad C - B = 3.
\end{equation*}
Therefore, the partial fraction decomposition is:
\begin{equation*}
\frac{5s + 3}{(s - 1)(s^2 + s + 1)} = \frac{5}{s - 1} + \frac{5s - 2}{s^2 + s + 1}.
\end{equation*}
Exercises Exercises
General Form.
Find the FORM of the partial fraction decomposition for each of the following. Make sure you completely factor each denominator before determining the decomposition. You need not find the values of the coefficients \(A,\) \(B,\) etc.
1.
\(\ds g(x) = \frac{17x - 11}{x^2(x-3)}\)
Answer. Answer
\begin{equation*}
g(x) = \frac{A}{x} + \frac{B}{x^2} + \frac{C}{x-3}
\end{equation*}
2.
\(\ds h(x) = \frac{x+12}{(x^2 - 4)^2}\)
Answer. Answer
\begin{equation*}
h(x) = \frac{A}{x-2} + \frac{B}{(x-2)^2} + \frac{C}{x+2} + \frac{D}{(x+2)^2}
\end{equation*}
3.
\(\ds r(x) = \frac{3x-14}{(x+1)(x^2 + 2x + 1)}\)
Answer. Answer
\begin{equation*}
r(x) = \frac{A}{x+1} + \frac{B}{(x+1)^2} + \frac{C}{(x+1)^3}
\end{equation*}
4.
\(\ds s(x) = \frac{111}{(x^2 - 9)(x^2+9)}\)
Answer. Answer
\begin{equation*}
s(x) = \frac{A}{x-3} + \frac{B}{x+3} + \frac{Cx+D}{x^2 + 9}
\end{equation*}
5.
\(\ds t(x) = \frac{2x^2 - 3x + 1}{(x^2 - 4)(x^2 + 4)}\)
Answer. Answer
\begin{equation*}
t(x) = \frac{A}{x-2} + \frac{B}{x+2} + \frac{Cx+D}{x^2 + 4}
\end{equation*}
6.
\(\ds u(x) = \frac{3x^2 - 2x + 1}{(x^2 - 1)(x^2 + 1)}\)
Answer. Answer
\begin{equation*}
u(x) = \frac{A}{x-1} + \frac{B}{x+1} + \frac{Cx+D}{x^2 + 1}
\end{equation*}
7.
\(\ds v(x) = \frac{4x^2 - 5x + 2}{(x^2 - 2x + 1)^2}\)
Answer. Answer
\begin{equation*}
v(x) = \frac{A}{x-1} + \frac{B}{(x-1)^2} + \frac{C}{x+1} + \frac{D}{(x+1)^2}
\end{equation*}
8.
\(\ds w(x) = \frac{5x^2 - 3x + 1}{x^4 - 16}\)
Answer. Answer
\begin{equation*}
w(x) = \frac{A}{x-2} + \frac{B}{x+2} + \frac{Cx+D}{x^2 + 4}
\end{equation*}
9.
\(\ds v(x) = \frac{x^5 - 3x - 27}{x^3 - 2x^2 - 3x}\)
Answer. Answer
\begin{equation*}
v(x) = \frac{A}{x} + \frac{B}{x-3} + \frac{C}{x+1}
\end{equation*}
10.
\(\ds u(x) = \frac{8x^2 - 51x + 41}{x^2 - 6x + 5}\)
Answer. Answer
\begin{equation*}
u(x) = \frac{A}{x-5} + \frac{B}{x-1}
\end{equation*}
Partial Fraction Decomposition.
Find the partial fraction decomposition for each of the following rational functions.
11.
\(\ds f(x) = \frac{3x^2 - 2x + 1}{x^3 - 2x^2 - 3x}\)
Answer. Answer
\begin{equation*}
f(x) = \frac{1}{x} + \frac{1}{x-3} + \frac{1}{x+1}
\end{equation*}
12.
\(\ds g(x) = \frac{17x - 11}{x^2(x-3)}\)
Answer. Answer
\begin{equation*}
g(x) = \frac{1}{x} + \frac{1}{x^2} + \frac{1}{x-3}
\end{equation*}
13.
\(\ds h(x) = \frac{x+12}{(x^2 - 4)^2}\)
Answer. Answer
\begin{equation*}
h(x) = \frac{1}{x-2} + \frac{1}{(x-2)^2} + \frac{1}{x+2} + \frac{1}{(x+2)^2}
\end{equation*}
14.
\(\ds r(x) = \frac{3x-14}{(x+1)(x^2 + 2x + 1)}\)
Answer. Answer
\begin{equation*}
r(x) = \frac{1}{x+1} + \frac{1}{(x+1)^2} + \frac{1}{(x+1)^3}
\end{equation*}
15.
\(\ds s(x) = \frac{111}{(x^2 - 9)(x^2+9)}\)
Answer. Answer
\begin{equation*}
s(x) = \frac{1}{x-3} + \frac{1}{x+3} + \frac{1}{x^2 + 9}
\end{equation*}
16.
\(\ds t(x) = \frac{2x^2 - 3x + 1}{(x^2 - 4)(x^2 + 4)}\)
Answer. Answer
\begin{equation*}
t(x) = \frac{1}{x-2} + \frac{1}{x+2} + \frac{1}{x^2 + 4}
\end{equation*}
17.
\(\ds u(x) = \frac{3x^2 - 2x + 1}{(x^2 - 1)(x^2 + 1)}\)
Answer. Answer
\begin{equation*}
u(x) = \frac{1}{x-1} + \frac{1}{x+1} + \frac{1}{x^2 + 1}
\end{equation*}
18.
\(\ds v(x) = \frac{4x^2 - 5x + 2}{(x^2 - 2x + 1)^2}\)
Answer. Answer
\begin{equation*}
v(x) = \frac{1}{x-1} + \frac{1}{(x-1)^2} + \frac{1}{x+1} + \frac{1}{(x+1)^2}
\end{equation*}
19.
\(\ds w(x) = \frac{5x^2 - 3x + 1}{x^4 - 16}\)
Answer. Answer
\begin{equation*}
w(x) = \frac{1}{x-2} + \frac{1}{x+2} + \frac{1}{x^2 + 4}
\end{equation*}
20.
\(g(x) = \ds \frac{1}{x^2 - 5x+6}\)
Answer. Answer
\begin{equation*}
g(x) = \frac{1}{x-3} + \frac{-1}{x-2}
\end{equation*}
21.
\(h(x) = \ds \frac{4x+7}{x^2 - 7x}\)
Answer. Answer
\begin{equation*}
h(x) = \frac{-1}{x} + \frac{5}{x-7}
\end{equation*}
22.
\(r(x) = \ds \frac{20x^2+65x+115}{(x^2+9)(x+11)}\)
Answer. Answer
\begin{equation*}
r(x) = \frac{5}{x+11} + \frac{15x+C}{x^2+9}
\end{equation*}
23.
\(s(x) = \ds \frac{3x^2+5x+7}{(x^2+4)(x^2+16)}\)
Answer. Answer
\begin{equation*}
s(x) = \frac{1}{x^2+4} + \frac{2}{x^2+16}
\end{equation*}
24.
\(t(x) = \ds \frac{2x^2+3x+5}{(x^2+1)(x^2+4)}\)
Answer. Answer
\begin{equation*}
t(x) = \frac{1}{x^2+1} + \frac{1}{x^2+4}
\end{equation*}
You have attempted
of
activities on this page.